Bi‐Oblique Dynamic Proximal Ulnar Osteotomy: Surgical Technique and Clinical Outcome in 86 Dogs. Issue 3 (24th March 2016) - Caron, Alexandre; Fitzpatrick, Noel
Abstract : Objective: To describe the technique of bi‐oblique dynamic proximal ulnar osteotomy (BODPUO) and report the clinical outcome in a series of dog with medial compartment disease and other developmental elbow diseases. Study Design: Retrospective case series. Animals: Dogs (n=86; 120 elbows) treated for elbow disease with BODPUO. Methods: Medical records and diagnostic images were reviewed. Type and frequency of complications and treatment required were recorded. Force plate data were reported in dogs for which data had been recorded preoperatively and at follow‐up. Results: Mean (standard deviation) final follow‐up was 23.4 (35.6) weeks. There were minor complications in 15 elbows (12%, 14 dogs). There were no major complications. The caudo‐cranial and latero‐medial mean osteotomy angles were 55° (7°) and 48° (10°), respectively. The most caudo‐proximal point of the osteotomy was located at a mean of 39% (5%) of the total ulnar length from the olecranon. Sixty of 68 elbows (88%) were considered healed by 4 months postoperative based on radiographs. Subjective lameness scores were significantly decreased by final follow‐up for all dogs. For dogs treated with BODPUO alone for medial compartment disease, peak vertical force was significantly higher at 6 months postoperative. Conclusion: Dogs with medial compartment disease undergoing BODPUO showed clinical improvement in the 6 month follow‐up. No complications required surgical intervention.